Potential and challenges for learning during acute medical/surgical placement for intellectual disability, mental health and midwifery students. (January 2018) - Mc Carthy, Jane; Graham, Margaret M.; Tuohy, Dympna; O'Brien, Brid; Fahy, Anne; Hennessy, Therese; O'Sullivan, Deirdre; Markey, Kathleen
Abstract: In Ireland nursing and midwifery degree programmes involve four pathways to registration. Three of which, intellectual disability and mental health nursing and midwifery require students to undertake acute medical/surgical placements offering learning opportunities caring for patients with complex needs in settings beyond their core discipline. This paper focuses on findings from a descriptive qualitative study exploring intellectual disability and mental health nursing and midwifery students experiences of such placements. Data analysis identified three themes: Getting ready, Navigating the way and Getting through. Feelings of stress and uncertainty are described by participants when moving from familiarity within a chosen discipline to an unfamiliar environment. Findings have influenced specific placement structures with local health service partners. While our study focuses on an Irish context, findings have relevance for student education in other jurisdictions. Enhancing preparation and support for students undertaking unfamiliar placements needs to be a constant endeavour. Such foundations will foster valuable experiences where students can feel part of a team, gain confidence, enhance skills and transfer meaningful learning to their core practice discipline. Further research is needed to explore the views of preceptors, ward managers and Clinical Placement Coordinators. Highlights: Acute medical/surgical placements provide valuable learning for mental health, intellectual disability and midwifery students. Reducing apprehension, feeling part of a team and confidence building are essential for practice learning. Strategies to help students navigate and make sense of practice experiences need to be considered in maximising learning.